Hungarian Monitoring, 17 January 1990 . [Magyar rádiófigyelő], 1990. január 17 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Summary of Azerbaijan news - Protest actions in Silesian mines - Government crisis in the GDR - Overview of the increasingly troubled situation in Romania Domestic Affairs: - Toshiki's visit - Dunagate: Interior Ministry internal security service head resigns - Gyula Horn in Rome - Health of guest workers in Tengiz - Overseeing radio and TV - Retrial discussions in the Pócspetri case - Mass graves in Timisoara Economy: - Hungarian Democratic Forum (MDF)'s economic delegation in negotiations in Moscow - Agricultural cooperative lands sold for peanuts - Trade minister Tamás Beck suspends exports calculated fully in rubles Külpolitika: - Azerbajdzsáni beszámoló - Tiltakozó akciók a sziléziai bányákban - Kormányválság az NDK-ban - Helyzetkép az egyre zavarosabb romániai helyzetről Belpolitika: - Toshiki látogatás - Dunagate: lemondott a BM belső biztonsági szolgálatának vezetője - Horn Gyula Rómában - A tengizi vendégmunkások egészségi állapota - Rádió és Tv felügyelet - Pócspetri-ügy perújítási tárgyalása - Tömegsírok Temesvárott Gazdaság: - Moszkvában tárgyal az MDF gazdasági delegációja - Bagóért árulják ki a tsz-földeket - Beck Tamás kereskedelmi miniszter felfüggesztette a teljes rubelelszámolású exportot